Quand les actes agricoles sont au care et au compagnonnage : L’exemple de la biodynamie - Foyer, Jean; Hermesse, Julie; Hecquet, Corentin (Anthropologica, 2020)
This article proposes to extend the analysis of the breakdown of utilitarian and materialistic human-animal relations to the plant domain. To do this, we will compare the theoretical corpuses on “care” and the “plant turn” with our own field data on biodynamic viticulture in France. The aim is to show that sensitive relations to agricultural plants based on care, companionship, and even spirituality must not be exoticised and reserved for a distant other. Indeed, beyond the logics of conservation and reproduction, the recognition of a certain agency of plants, the establishment of different forms of communication with them, and, more generally, the blurring of the ontological differentiation between humans and agricultural plants are behaviours that can also be observed in the Western context.